The barriers of women who have sex with women in access to health in Brazil (Research, Society and Development, 2021)
Lesbian and bisexual women are an invisible minority when they’re seeking sexual health care services. Due to this invisibility within an ancient culture of heteronormativity, the sexual health of lesbian and bisexual women is often poorly managed by health professionals. Based on this assumption, this article aims to identify the difficulties in the doctor-patient relationship and assess the barriers to access faced by women who have sex with women. The study is a narrative bibliographic review, the survey of scientific publications was in the databases: Lilacs, PubMed, Medline and SciELO. Through research, it appears that the lower demand for health services is often associated with the existence of discrimination in health services and the lack of preparation of professionals to deal with the existing specificities. In addition, there is a lower frequency of gynecological exams, tests and breast cancer prevention among lesbian and bisexual women. Finally, it is necessary that more studies are carried out in order to put such difficulties in numbers and generate policies and strategies to improve gynecological care for women who have sex with women.